Modeling and Predicting Changes in Pulmonary Vascular Resistance After Left Ventricular Assist Device Implantation - Gulati, Gaurav. (Tufts University. Tisch Library., 2020)
Thesis (M.S.)--Tufts University, 2020.; Submitted to the Dept. of Clinical & Translational Science.; Advisor: David Kent.; Committee: Robin Ruthazer, and Michael Kiernan.; Keyword: Medicine.